4e-3(2e-2)=3(e+8)

Simple and best practice solution for 4e-3(2e-2)=3(e+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4e-3(2e-2)=3(e+8) equation:


Simplifying
4e + -3(2e + -2) = 3(e + 8)

Reorder the terms:
4e + -3(-2 + 2e) = 3(e + 8)
4e + (-2 * -3 + 2e * -3) = 3(e + 8)
4e + (6 + -6e) = 3(e + 8)

Reorder the terms:
6 + 4e + -6e = 3(e + 8)

Combine like terms: 4e + -6e = -2e
6 + -2e = 3(e + 8)

Reorder the terms:
6 + -2e = 3(8 + e)
6 + -2e = (8 * 3 + e * 3)
6 + -2e = (24 + 3e)

Solving
6 + -2e = 24 + 3e

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-3e' to each side of the equation.
6 + -2e + -3e = 24 + 3e + -3e

Combine like terms: -2e + -3e = -5e
6 + -5e = 24 + 3e + -3e

Combine like terms: 3e + -3e = 0
6 + -5e = 24 + 0
6 + -5e = 24

Add '-6' to each side of the equation.
6 + -6 + -5e = 24 + -6

Combine like terms: 6 + -6 = 0
0 + -5e = 24 + -6
-5e = 24 + -6

Combine like terms: 24 + -6 = 18
-5e = 18

Divide each side by '-5'.
e = -3.6

Simplifying
e = -3.6

See similar equations:

| 3(4d-2)=3(d-2) | | 5(c-2)=3(c+6) | | 15x-4+4x+5+65= | | 7(b-4)=5(b-2) | | 2(3b-4)=5(b-1) | | 3(3a+1)=30 | | 4(1/3x-1/4)+4/3x/3+1=6 | | 8-4=6z-8z | | k^3+2k^2-10k-20=0 | | 7(x+2)=7x+10 | | z^4-26z^2+25=0 | | 5x-10-2=13 | | 1/2x16=0 | | p^(2/3)+p^(1/2) | | 3x-7+5=16 | | (x^2-81)/(x^2-6x-27)*(x+3)/x | | 98x+456= | | x^3-4x=85008 | | 250=(50-3)+x | | s=2x+t/r | | x/5-x=1/5 | | 0.5y=30 | | -6(x-2)+4(8x-12)=68 | | 6ln(3x)=12 | | -6(x-2)-4(8x-12)=68 | | 3x-2=7x+8 | | 4(-6+x)=5x+1/4 | | h=4a-3 | | 1/6-18/12 | | 7-3(5t-7)=67 | | 5x^2y^4-80x^4y^2=0 | | 1=23*t+2-1-2+1-23*t+2*t-1*t |

Equations solver categories